Nanotubos de carbono interagindo com vitaminaS B3 e C: um estudo de primeiros princípios - Menezes, Vivian Machado de (2008)
This work presents a theoretical study about the interaction between pristine or functionalized B3 and C vitamins with semiconducting carbon nanotubes (8,0) through first principles simulations. We evaluate the structural and electronic properties of the B3 and C vitamins adsorbed on nanotubes, using the density functional theory with the SIESTA computational code. We observe that there is a strong dependence of the interaction between B3 and C vitamins with the carbon nanotubes subject to the modification of the original structure (functionalization) of these vitamins. For the configurations which the pristine vitamins are adsorbed on the nanotubes, the interaction occurs by physical adsorption. On the other hand, we verify that in the case of functionalized vitamins, the adsorption occurs by a chemical interaction with the nanotube. In the case of vitamins interacting by physical adsorption, no significant changes in the electronics properties are observed. However, for the chemical adsorption of the vitamins on the tube, we notice that the changes in the electronic properties are dependent of how the molecules are functionalized, being able to create half-filled levels in the Fermi energy region, or even though to restore the electronic structure of the semiconducting carbon nanotube. These results show that carbon nanotubes can be considered chemical agents for attachment or selectivity for organic molecules, as in the case of the B3 and C vitamins.